Analisis Faktor yang Mempengaruhi Penerapan Akuntansi pada UMKM - Fahrudin, Imam; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2023)
The research objective is to examine the effect of perceptions about accounting, accounting knowledge, and technological knowledge on the application of accounting. The test was carried out on accounting students of the Accounting Study Program, Faculty of Economics and Business, Udayana University who run Micro, Small & Medium Enterprises (MSMEs). Samples were selected with saturated sample technique. The data collection method in this study was participatory observation method, data were analyzed using Ordinary Least Square (OLS). The results of the analysis show that perceptions about accounting, knowledge of accounting, and knowledge of technology have an effect on the application of accounting. This research has implications for all parties who need information regarding the importance of perceptions about accounting, accounting knowledge and technological knowledge in accounting application. Keywords: Perceptions About Accounting; Accounting Knowledge; Technological Knowledge; Accounting Application